Analyzing Methods Best Used In Translating Song Swimming Pools (Drank) – Extended Version by Kendrick Lamar - Christmas, Glorio; Ridhwan, Moehamad; Ningrum, Sulistya (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2025)
ABSTRACT: This study analysed the most effective translation methods for Kendrick Lamar’s rap song “Swimming Pools (Drank) – Extended Version,” focusing on bridging linguistic and cultural gaps in song translation. Using Molina & Albir’s translation techniques as the theoretical framework, the research explored how the cultural nuances and lyrical complexity of rap music could be conveyed accurately in the target language. The qualitative approach involved a detailed examination of the song’s lyrics, considering both contextual and cultural factors, and applying selected techniques from the eighteen methods proposed by Molina & Albir. The findings highlighted that the most frequently used translation techniques were amplification, adaptation, substitution, and particularization, as these methods were essential for maintaining the original song’s stylistic elements, cultural essence, and semantic structure. The study aimed to provide insights for English and Tourism students, encouraging a deeper understanding of translation methods and fostering creative approaches for future translation projects. The results were expected to dispel misconceptions about Indonesian rap culture and served as a reference for translating culturally rich artistic expressions. Keywords: translation methods, Molina & Albir techniques, song translation, cultural adaptation, amplification   DOI: https://zenodo.org/records/18087462